The Effect of Game Addiction and Perceived Value on App Purchase Intention of Roblox Game Players in Indonesia - Nabil Zidane Al-Munir; Hisbulloh Edgaritoh; Rayhan Aimar Nawawi; I Gusti Bagus Prabu Vedayana Priharta; Muhammad Fajar Wahyudi Rahman (Journal of Digital Business and Innovation Management, 2026)
The freemium model has positioned in-app purchases as a primary monetization mechanism in digital games, including Roblox as a user-generated gaming platform. This study examines the effects of game addiction and perceived value on in-app purchase intention among Roblox players in Indonesia. Using a quantitative explanatory approach, data were collected through a cross-sectional survey of Roblox players in Indonesia and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that both game addiction and perceived value have positive and significant effects on in-app purchase intention. However, perceived value exerts a stronger influence than game addiction, indicating that players’ purchasing decisions are more strongly driven by evaluations of enjoyment, social recognition, functional performance, and price fairness rather than addictive engagement alone. These findings contribute to the understanding of digital consumer behavior in user-generated gaming environments and provide insights for value-oriented monetization strategies.